2004
DOI: 10.1159/000077123
|View full text |Cite
|
Sign up to set email alerts
|

Study of Potassium Phytate Effects on Decreasing Urinary Calcium in Rats

Abstract: Background: Phytate as sodium salt has been used at high doses to treat stone-former patients with idiopathic hypercalciuria. The experimental and clinical hypocalciuric effects of dietary fiber have also been assigned to the presence of phytate as calcium-magnesium salt (phytin). As a consequence of the additional interest in phytate due to its capacity as crystallization inhibitor, now a study of the effects of potassium phytate on urinary calcium excretion is presented and compared with the effects caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In rats, potassium phytate reduces calcium excretion. 59 The Nurses' Health Study II 5 reported a strong inverse relationship between phytate intake and stone risk, with the women in the highest quintile of phytate intake having a 36% lower risk of stone formation. However, in men, there was no relationship between phytate intake and stone risk.…”
Section: Notesmentioning
confidence: 99%
“…In rats, potassium phytate reduces calcium excretion. 59 The Nurses' Health Study II 5 reported a strong inverse relationship between phytate intake and stone risk, with the women in the highest quintile of phytate intake having a 36% lower risk of stone formation. However, in men, there was no relationship between phytate intake and stone risk.…”
Section: Notesmentioning
confidence: 99%
“…Both molecules are crystallization inhibitors, and they work synergistically with pH correctors, reducing the nucleation and crystallization. [22][23][24][25][26][27] In addition, the survival analyses showed that, once the urinary pH became nonlithogenic, free-survival rates of selfreported colic events improved. Although this result should be interpreted with caution, it shows a relationship between the reduction in renal lithiasis-related events and a nonlithogenic pH.…”
Section: Discussionmentioning
confidence: 99%
“…Both molecules are crystallization inhibitors, and they work synergistically with pH correctors, reducing the nucleation and crystallization. 2227…”
Section: Discussionmentioning
confidence: 99%